The Impact of Climate Change on Agricultural Production and Food Sustainability: Strategies for Adaptation and Resilience - Hasan, Muhammad Chairil (Cebong Journal, 2024)
Climate change has become a rapidly growing global challenge and has multidimensional impacts, including on the agricultural sector and food sustainability. This study aims to evaluate the potential impacts of climate change, particularly changes in temperature, rainfall, and CO2 concentrations, on rice production in the context of certain regions. A mathematical formulation model is used to analyze and predict these impacts. Through numerical analysis, it can be identified that changes in average temperature, rainfall, and CO2 concentration contribute to variations in rice production from year to year. The results show that even a slight increase in average temperature has a relatively small impact on production. However, decreased rainfall and increased CO2 concentrations have a more significant impact on agricultural yields. This research shows that climate change has serious implications for agriculture and food security. With changes in climatological factors, comprehensive adaptation and mitigation measures are becoming increasingly important. These findings provide important guidance for farmers, policy makers and stakeholders in designing agricultural strategies that are sustainable, adaptive and resilient to climate change.